Safety assessment of high doses of vaporized oxalic acid on honey bee worker health and queen quality - Tellarini Prieto, Emilio Enrique; Pietropaoli, Marco; Camus, Ylona; Polizel Camilli, Marcelo; Raza, Muhammad Fahim; Jose, Midhun Sebastian; Obshta, Oleksii; Bezerra da Silva, Marina Carla; Kozii, Ivanna; Moshynskyy, Igor; Edirithilake, Thanuri L.K.; Baril, Erin; et al. (Frontiers in Bee Science, 2024)
The ectoparasitic mite of honey bees, Varroa destructor, is a leading cause of honey bee colony loss worldwide. Oxalic acid (OA) is one of the most popular treatments for Varroa management. However, the potential toxicity of OA to adult bees and queens is still inconclusive. To investigate further, we exposed 32 colonies to incremental doses (0, 5, 10 or 20 g per colony) of vaporized OA once per week over four consecutive weeks and we monitored the acute and long-term toxicity. We investigated the short-term effects of OA administration by evaluating adult bee mortality, brood production, and population size. Next, we evaluated the long-term effects of OA application on both worker bees and queens. Regarding workers, we investigated their ability to rear new queens. As for queens, we measured acceptance, performance, and sperm quality. We found that repeated application of vaporized OA, at up to 20 times the label dose (1g per single brood chamber colony), had no significant short-term nor long-term negative effects on colony nor queen health, with the exception of a short-term increase in adult bee mortality in the 20 g OA-treated group. Overall, our results support that higher-than-label doses of OA, up to 20 g repeated four times at seven-day intervals, are safe for honey bee colonies undergoing treatment for varroa mites.